5PSQ-082 Cyclophosphamide therapy in children with nephrotic syndrome. (2nd March 2018) - Son, R; Hwang, D; Jung, AH; Lim, JM; Jung, SH; Suh, SY; Hahn, HJ; Cho, YS; Park, EJ; Cheong, HI
Abstract : Background: Cyclophosphamide (CPM), one of the corticosteroid-sparing agents, is a therapeutic option for children with frequently relapsing (FRNS) or steroid-dependent nephrotic syndrome (SDNS). There is a lack of paediatric study data in the country, although the Kidney Disease Improving Global Outcomes guideline recommends the use of CPM. Purpose: To provide data on th eefficacy of CPM treatment in paediatric patients with FRNS/SDNS and identify the parameters associated with sustained remission and relapse frequency. Material and methods: Total number of participants was 72, who were diagnosed as FRNS/SDNS and treated with 12 weeks single course of oral CPM from 2005 to 2015 in a mono-centre, retrospectively. The effectiveness of CPM was assessed by the 2 year and the 5 year cumulative sustained remission rate and the comparison of relapse frequency before and after CPM. The Cox proportional hazard model was used to adjust multivariate analysis to assess parameters associated with sustained remission. Multiple regression analysis was performed to identify relapse frequency measurement factors. Adverse drug reaction (ADR) recorded in electronic medical records was used for safety evaluation. Results: The mean ages at the onset of syndrome and at the time of CPM treatment were 4.54±2.72 and 6.69±2.88 years, respectively. The mean dose of CPM was 2.11±0.27 mg/kg/day, and the mean duration of treatment was 11.65±0.95 weeks. Thereafter, the median follow-up period was 4.79±2.34 years. The 2 year cumulative sustained remission rate was 37.9% (n=25) and that of the 5 year period was 27.6% (n=8). Relapse frequency before and after CPM was 3.03±1.42 per year and 1.36±0.95 per year (p<0.001), respectively. In Cox regression, the leukopaenia event can be considered to increase the sustained remission rate after treatment (p=0.014, HR=0.412, 95% CI: 0.204 to 0.833). A shorter interval between nephrotic syndrome onset and CPM treatment initiation could be considered as a decreasing factor of relapse frequency (β=−0.379, p=0.005). The most frequent ADR was CPM-induced leukopaenia (n=21, 29.2%), but any ADR causing treatment discontinuation was not reported. Conclusion: CPM is quite an effective and safe alternative treatment for children with FRNS/SDNS. Sustained remission is associated with the leukopaenia event. The interval from onset to CPM is associated with relapse frequency. References and/or Acknowledgements: KDIGO 2012guideline No conflict of interest